Adobe Photoshop CC for photographers 2018 edition a professional image editor's guide to the creative use of Photoshop for the Macintosh and PC - Evening, Martin (Routledge, 2018)
Martin Evening, Photoshop hall-of-famer and acclaimed digital imaging professional, has revamped his much-admired Photoshop for Photographers book for an eleventh edition, to include detailed instruction for all of the updates to Photoshop CC on Adobe's Creative Cloud. This comprehensive guide covers all the tools and techniques serious photographers need to know when using Photoshop, from workflow guidance to core skills to advanced techniques for professional results. Using clear, succinct instruction and real world examples, this guide is the essential reference for Photoshop users of all levels